Intercultural Aesthetics
VI, 218 p.
Keywords: In this book the editors brought together outstanding articles concerning intercultural aesthetics. The concept ‘Intercultural aesthetics’ creates a home space for an artistic cross-fertilization between cultures, and for heterogeneity, but it is also firmly linked with the intercultural turn within Western and non-Western philosophy. The book is divided into two parts, yet one can sense a clear unity throughout the whole book. This unity is related to the underlying subject that the different authors, each in their own way and from their own background, try to reveal. They use related, and overlapping terms such as ‘the suchness of things’, ‘dancing and shaping lives’, ‘presenting a meaning beyond words, presenting the unpresentable, experiencing’, in order to bring to our awareness the genuine importance of the non-conceptual, next to the conceptual. Several authors moreover take on a reflective, and at times even a self-reflective stance, pointing to the intrinsic relation between cultural aesthetics and ethics, making this book unique in its kind.